Optimal HEN with PHEs for Carbon Dioxide Capture by Amine Absorption Unit at Coal Fired Power Station - Petro Kapustenko; Jirí Jaromír Klemeš; Olexander Perevertaylenko; Leonid Tovazhnyanskyy; Olga Arsenyeva; Eugeny Klochok; Valeriy Ved (Chemical Engineering Transactions, 2023)
The CO2 capture processes are of growing interest to scholars in the struggle against global warming, and for the use of CO2 in the production of clean fuels, chemicals, plastics, and other materials. The post-combustion capture of carbon dioxide from flue gases with monoethanolamine (MEA) Absorption Desorption Unit (ADU) is studied with Process Integration methodology. The optimal structure of the Heat Exchanger Network (HEN) is determined. The study aims to find economically viable options for desorption column parameters by computer modelling and to evaluate the use of novel compact plate heat exchangers (PHEs) with intensified heat transfer. Based on a presented case study, the variation of temperature approach on rich/lean heat exchanger and its influence on heat consumption is discussed. The effect of minimal temperature difference in HEN on the investment cost and its energy efficiency is analyzed. It is shown that the optimal value of minimal temperature difference for HEN with PHEs is 7 °C, which is two times smaller than for HEN based on shell and tube heat exchangers. The use of PHEs in HEN ADU at the same or even smaller purchased cost of heat exchangers saves up to 24 % energy compared to the base case. It is 13 % higher than for the option based on the use of conventional tubular heat exchangers.